Adult-onset Still's disease triggered by pregnancy. Issue 2 (3rd April 2019) - Abdulkarim, Saleem; Otieno, Fredrick; Ali, Sayed K.
Abstract: Adult-onset Still's disease (AOSD) is an inflammatory disorder with arthritis, quotidian fever, evanescent rash, elevated white cell count, elevated ferritin, and abnormal liver function tests. The diagnosis requires the exclusion of other inflammatory, infectious, and malignant conditions. Onset of AOSD, though rare, has been known to occur in pregnancy. We present a 28-year-old woman diagnosed with AOSD at 3 months gestation.